2021
DOI: 10.7554/elife.67776
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis defines heterogeneity of the murine pancreatic ductal tree

Abstract: To study disease development, an inventory of an organ's cell types and understanding of physiologic function is paramount. Here, we performed single-cell RNA sequencing to examine heterogeneity of murine pancreatic duct cells, pancreatobiliary cells, and intrapancreatic bile duct cells. We describe an epithelial-mesenchymal transitory axis in our three pancreatic duct subpopulations and identify osteopontin as a regulator of this fate decision as well as human duct cell dedifferentiation. Our results further … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 85 publications
2
12
1
Order By: Relevance
“…Compared with Hendley et al’s study [ 45 ], we did not identify the subpopulations of the pancreatic ductal cells; this is considered to be due to the insufficient cell numbers. More recently, Ma et al identified cell populations arising from ADM under conditions of chronic injury by combining lineage tracing and scRNA-seq technology [ 22 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Compared with Hendley et al’s study [ 45 ], we did not identify the subpopulations of the pancreatic ductal cells; this is considered to be due to the insufficient cell numbers. More recently, Ma et al identified cell populations arising from ADM under conditions of chronic injury by combining lineage tracing and scRNA-seq technology [ 22 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Next, we plotted the histograms for the EMT scores of various single-cell RNA-seq datasets to decipher the heterogeneity seen along the EMP spectrum across a variety of biological contexts: 1. human embryonic stem-cell-derived progenitor cells differentiating to endoderm (GSE75748) [ 63 ]; 2. human fetal pituitary gland development including progenitors of many endocrine cell types and subtypes (GSE142653) [ 64 ]; 3. cells from different tissues and organs of E9.5 to E11.5 mouse embryos (GSE87038) [ 65 ]; 4. MCF10A cells treated with TGF-β for varying durations and exhibiting a gradual change in their EMT status (PRJNA698642) [ 66 ]; 5. murine pancreatic duct cells with variations along the EMP spectrum (GSE159343) [ 67 ]; 6. EpCAM+ and EpCAM- squamous skin carcinoma cells with varied epithelial and/or mesenchymal features (GSE110357) [ 68 ]; 7. cells from oral cavity tumors/head and neck squamous cell carcinoma (GSE103322) [ 17 ]; 8. human colorectal cancer cell lines and tumors (GSE81861) [ 69 ], and 9. mouse hair follicle stem cells and transit-amplifying cells (GSE90848) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we plotted the histograms for EMT scores of various single-cell RNA-seq datasets to decipher the heterogeneity seen along the EMP spectrum across a variety of biological contexts: 1. human embryonic stem-cell-derived progenitor cells differentiating to endoderm (GSE75748) (Chu et al, 2016); 2. human fetal pituitary gland development including progenitors of many endocrine cell types and subtypes (GSE142653) (Zhang et al, 2020); 3. cells from different tissues and organs of E9.5 to E11.5 mouse embryos (GSE87038) (Dong et al, 2018); 4. MCF10A cells treated with TGF-β for varying durations and exhibiting a gradual change in their EMT status (PRJNA698642) (Deshmukh et al, 2021); 5. murine pancreatic duct cells with variations along the EMP spectrum (GSE159343) (Hendley et al, 2021); 6. EpCAM+ and EpCAM-squamous skin carcinoma cells with varied epithelial and/or mesenchymal features (GSE110357) (Pastushenko et al, 2018); 7. cells from oral cavity tumors/head and neck squamous cell carcinoma (GSE103322) (Puram et al, 2017); 8. human colorectal cancer cell lines and tumors (GSE81861) (Li et al, 2017), and; 9. mouse hair follicle stem cells and transit-amplifying cells (GSE90848) (Yang et al, 2017).…”
Section: Single-cell Rna-seq Data Analysis Reveals Heterogeneity Along the Emp Spectrummentioning
confidence: 99%